PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN JASA KAMAR DI IMELDA HOTEL – WATERPARK – CONVENTION PADANG - Damayanti, Vivin (RC-INSTITUT, 2019)
This research starts from the results of pre-research observations of guests staying at Imelda Hotel - Waterpark - Convention Padang, researchers found problems including;  1) Low occupancy rates at Imelda Hotel - Waterpark - Convention Padang, 2) Room rates at Imelda Hotel - Waterpark - Convention Padang are expensive, 3) Imelda Hotel Location - Waterpark - Convention Padang is less strategic, far from the city center and shopping center. This type of research is quantitative descriptive with a causal associative approach.  The number of samples in this study amounted to 94 people taken using purposive sampling technique.  Data retrieval technique is done by distributing questionnaires (questionnaires) using a Likert scale that has been tested for validity and reliability.  The analysis technique uses the help of the computer program SPSS 16.0 through multiple linear regression tests. Based on the research that has been done, the results are as follows: (1) Prices are in a bad category (74%), (2) Locations are in a bad category (85%), (3) Purchasing decisions are in a very good category (97%  ), (4) The effect of price and location on room service purchase decisions is 40.3% while 59.7% is influenced by other factors.